Perkembangan Penggunaan Internet of Things (IoT) Dalam Industri Pembinaan Di Malaysia: Persepsi Pihak Kontraktor - Wan Mohd Khouluddin, Wan Muhammad Ikmal; Omar, Roshartini; Nasid Masrom, Md Asrul; Ta Wee, Seow (Research in Management of Technology and Business, 2023)
The construction sector is vital to Malaysia’s expanding economy. However, the construction industry has been criticized for its reliance on technology and management problems. The advent of the Internet of Things (IoT) is a relatively new phenomenon in this sector. This technology first appeared after the transition to the 4.0 industrial revolution, which established IoT as the backbone of the new system. This research aims to investigate the contractors’ awareness of the IoT’s progress, the challenges while using IoT technology, and the ways to enhance contractors’ use of the platform. The study population consists of 71 G7 contractors working in the Sepang, Selangor area. The data for this study will be gathered using quantitative techniques. There have been 30 total responses or a 51% completion rate. In this analysis, the researchers discovered that contractors’ awareness of IoT advancement was most strongly associated with their access to effective communication tools. The contractor also struggles with a lack of skilled labor when dealing with IoT. Next, expanding IoT- focused campaigns and events was voted as the most effective strategy for boosting the adoption of the technology within the building industry. The use of IoT needs to be increased to increase national income in line with current technological developments to improve the standard of living of the population. The study’s findings are meant to be used by aspiring academics and working professionals in the field.